"Studies on physical and mechanical properties of untreated (raw) and treated areca leaf sheaths". (10th November 2021) - Banagar, Ashok; Chikkol, Srinivasa Venkateshappa; Bennehalli, Basavaraju
ABSTRACT: Presently, the world is looking for non-polluting, non-toxic, renewable, low density, corrosion resistant, eco-friendly, and low-cost material as replacement for the most challenging elements like plastics and its derivatives. Meanwhile, some of the composites were also made with some challenging facts concerning biodegradability properties. Thereby this is an attempt to make use of natural sources in the composite preparation and reduce the extra burden caused by unwanted materials on the earth. In this study, economical filler materials such as untreated and alkali treated Areca Leaf Sheaths (ALS) are studied for physical and mechanical characterization. Among these, alkali treated-oven dried ALS samples have shown improved results in terms of density, thickness and mechanical properties as compared to untreated-sun dried samples. From XRD, FTIR, and SEM analysis, it was concluded that, the surface modification will enhance the micro-fibrillation of the areca leaf sheath fibers and this will increase the mechanical properties.